Melt electrowritten scaffold architectures to mimic tissue mechanics and guide neo-tissue orientation - Tornifoglio, Brooke; Kelly, Daniel; Hoey, David; Lally, Caitriona (My University, 2024)
All human tissues present with unique mechanical properties critical to their function. This is achieved in part through the specific architecture of the extracellular matrix (ECM) fibres within each tissue. An example of this is seen in the walls of the vasculature where each layer presents with a unique ECM orientation critical to its functions. Current adopted vascular grafts to bypass a stenosed/damaged vessel fail to recapitulate this unique mechanical behaviour, particularly in the case of small diameter vessels (<6 mm), leading to failure. Therefore, in this study, melt-electrowriting (MEW) was adopted to produce a range of fibrous scaffolds to mimic the extracellular matrix (ECM) architecture of the tunica media of the vasculature, in an attempt to match the mechanical and biological behaviour of the native porcine tissue. Initially, the range of collagen architectures within the native vessel was determined, and subsequently replicated using MEW (winding angles (WA) 45°, 26.5°, 18.4°, 11.3°). These scaffolds recapitulated the anisotropic, non-linear mechanical behaviour of native carotid blood vessels. Moreover, these grafts facilitated human mesenchymal stem cell (hMSC) infiltration, differentiation, and ECM deposition that was independent of WA. The bioinspired MEW fibre architecture promoted cell alignment and preferential neo-tissue orientation in a manner similar to that seen in native tissue, particularly for WA 18.4° and 11.3°, which is a mandatory requirement for long-term survival of the regenerated tissue post-scaffold degradation. Lastly, the WA 18.4° was translated to a tubular graft and was shown to mirror the mechanical behaviour of small diameter vessels within physiological strain. Taken together, this study demonstrates the capacity to use MEW to fabricate bioinspired scaffolds to mimic the tunica media of vessels and recapitulate vascular mechanics which could act as a framework for small diameter graft development to guide tissue regeneration and orientation.
PUBLISHED
Keywords: Aspect ratio; Compliance; Contact guidance; ECM organisation; Melt electrowriting; Small diameter vascular graft; Vascular regeneration